Cardiovascular Disease in the Elderly - Messerli, Franz H. (Springer US, 1993)
That geriatric cardiology has become a science and clinical discipline in its own rights is beyond dispute. Most cardiac disorders present with different symptoms and signs, require a different diagnostic and therapeutic approach, and also have a different prognosis in the elderly as compared to younger patients. Cardiovascular Disease in the Elderly provides a comprehensive, up-to-date guide to the physician, representing a pioneering work in this increasingly complex area. For this third edition most of the chapters have been completely rewritten, some by different authors. Four new chapters have been added, dealing with cardiac transplantation, invasive cardiovascular procedures, dietary considerations and ethical considerations. It cannot be denied that invasive procedures and transplantation are highly controversial in this area, and the ethical dilemmas involved are ably discussed by Dr Davis and associates. All chapters are supplied with a thorough list of references, making this third edition of Cardiovascular Disease in the Elderly the most thorough, concise guide for the practicing physician
Keywords: Cardiology; Kardiovaskuläre Krankheit; Alter; Aufsatzsammlung